PERAN FASILITATOR PENDAMPING DALAM PENGEMBANGAN, PEMBUATAN BANNER PADA UMKM SEMBAKO - Lilisnawati; Yorina An’ guna bansa; Deka veronika; Mustika (Jurnal Riset Multidisiplin Edukasi, 2025)
This study discusses the role of the facilitator in developing MSMEs at PT. BTPN Syariah In MMS Muarasabak Timur, this company is engaged in Islamic finance which has a program that focuses on developing customer MSMEs run by facilitators, the purpose of the study is to identify the role of facilitators in developing MSMEs, analyze the obstacles faced by facilitators during the MSME development process, and find solutions to these obstacles. Data collection methods involve observation, interviews, and literature studies, while data analysis is carried out descriptively qualitatively. This study provides an in-depth understanding of the role, obstacles, and solutions of mentors in the context of MSME development at PT BTPN Syariah in MMS Muara Sabak Timur.